Kajian Fenomenologi Pemantauan Tumbuh Kembang Bayi oleh Kader Posyandu di Puskesmas Tosora - Tetti Surianti; Lisna Lisna (Journal Research of Nursing & Midwifery (JRNM), 2025)
Posyandu is an important health service unit that plays a crucial role in monitoring the growth and development of infants. The Posyandu cadres have a central role in providing education and health monitoring, yet the effectiveness of their role in this monitoring process has not been thoroughly analyzed. Therefore, it is important to further explore the roles and challenges faced by cadres in carrying out their duties. This study aims to examine the monitoring of infant growth and development by Posyandu cadres at Puskesmas Tosora, as well as the challenges they encounter in its implementation, to enhance understanding of the effectiveness of cadres' roles in this public health program. This research employs a qualitative approach with a phenomenological method, analyzed using the Colaizzi technique. Data were obtained through in-depth interviews with 8 informants directly involved in monitoring infant growth and development at Puskesmas Tosora. The results show that Posyandu cadres have a key role in monitoring infant growth and development, including weight measurement, height measurement, and immunization administration. However, they face challenges such as a lack of formal training, limited Posyandu facilities, and insufficient support from relevant stakeholders. Strategies to address these challenges include collaboration with healthcare workers and the use of local resources. Posyandu cadres play a vital role in monitoring infant growth and development. There is a need for enhanced training and facilities to support their role in optimizing child health services.